MOMENTUM AND CONTRARIAN STRATEGIES EVIDENCE IN VIETNAM STOCK MARKET - Nguyễn Thị Phương Thảo; Nguyễn Văn Anh (Tạp chí Khoa học Đại học Đà Lạt, 2012)
This study mainly investigates the investment performance of momentum strategy and contrarian strategy in Vietnam stock market from January 2007 to March 2011 by using the empirical methodology in Jegadeesh and Titman (1993). The empirical results show that during the period January, 2007 to March, 2011 momentum strategy works effectively over the horizon of 1, 5, 10, 20, 60 and 90 days,meanwhile, no contrarian strategy can make significant profit during the same horizon, which is quite different from other developed stock markets. Moreover, the results suggest that in Vietnam stock market it is better to limit the holding period in short term because momentum profit will decrease rapidly when holding period is longer and the best choice is limiting the trading and holding period to 5 days. Additionally, I find that buying high-volume winners and selling high-volume losers is more profitable than buying low-volume winners and selling low-volume losers